Detection of Suicidal Ideation in Social Media Through Content Analysis - K. Divya; Kona Namratha Blessy; Yarramsetty Lalasa Navya; Jonnala Kumar Swamy; Sammeta Manikanta (International Journal of Scientific Research in Science and Technology, 2024)
This article describes content analysis of text with to identify suicidal tendencies and types. This article also describes how to make a sentence classifier that uses a neural network created using various libraries created for machine learning in the Python programming language. Attention is paid to the problem of teenage suicide and «groups of death» in social networks, the search for ways to stop the propaganda of suicide among minors. Analysis of existing information about so-called «groups of death» and its distribution on the Internet.
Keywords: Content Analysis; Social Networks; Neural Networks; Machine Learning; Groups of Death; Python